Load Capacities of Steel and Concrete Composite Bridge Deck Slab with Haunch - Xiaoqing Xu; Yuqing Liu (Advances in Civil Engineering)
An innovative steel and concrete composite bridge deck slab using bent bars and epoxy as shear connectors was proposed. Four slab specimens with different types of concrete were fabricated and tested to study the load capacities of positive and negative moment regions of the slabs. The cracking and ultimate loads of the specimens were recorded and compared with the results calculated through the reinforced concrete theory and with the design load of the bridge deck slab. It was found that reinforced concrete theory can generally be applied for the proposed slab as well. The effectiveness of the shear connector design of the proposed slab was validated. Meanwhile, the unfavourable effect of the haunch on the shear capacities of the positive moment region of steel and concrete composite bridge deck slab was observed.